Red Raspberry Phenols Inhibit Angiogenesis: A Morphological and Subcellular Analysis Upon Human Endothelial Cells. Issue 7 (16th March 2016) - Sousa, M.; Machado, V.; Costa, R.; Figueira, M.E.; Sepodes, B.; Barata, P.; Ribeiro, L.; Soares, R.
ABSTRACT: Polyphenols are a class of natural compounds whose potential as antioxidant, anti‐inflammatory, and anti‐angiogenesis has been reported in many pathological conditions. Red raspberry extract, rich in polyphenols, has been reported to exert anti‐inflammatory effects and prevent cell proliferation in distinct animal models. However, the signaling pathways involved remain unknown. Herein, we used human microvascular endothelial cells (HMVECs) to determine the influence of red raspberry phenolic compound extract concentrations, ranging from 10 to 250 µg gallic acid equivalents (GAE)/mL, on endothelium viability (MTS assay), proliferation (BrdU incorporation), migration (injury assay), and capillary‐like structures formation (Matrigel assay). Protein expression in cell lysates was determined by Western blot analysis. We showed that red raspberry extracts reduced cell viability (GI50  = 87, 64 ± 6, 59 μg GAE/mL) and proliferation in a dose‐dependent manner. A significant abrogation of cells ability to migrate to injured areas, even at low concentrations, was observed by injury assay. Cell assembly into capillary‐like structures on Matrigel also decreased in a dose dependent‐manner for higher extract concentrations, as well as the number of branching points per unit of area. Protein expression analysis showed a dose‐dependent decrease in Phospho‐VEGFR2 expression, implying abrogation of VEGF signaling activity. We also showed for the first time that red raspberry phenolic compounds induce the rearrangement of filamentous actin cytoskeleton, with an isotropy increase found for higher testing concentrations. Taken together, our findings corroborate the anti‐angiogenic potential of red raspberry phenolic compounds and provide new insights into their mode of action upon endothelium. J. Cell. Biochem. 117: 1604–1612, 2016. © 2015 Wiley Periodicals, Inc. Abstract : We found that red raspberry phenolic compounds were able to prevent angiogenesis behaviour of endotelial cells, accompanied by decrease in VEGFR‐2 activity. These compounds also induced the rearrangement of filamentous actin cytoskeleton. These compounds are good candidates for anti‐angiogenic therapeutic approaches.